Corrosion Inhibition of Mild Steel in 1 M HCl Solution by Poly(o-aminothiophenol) and Poly(o-aminothiophenol)/CuO Nanocomposites - Anto Maria Jeraldin, U.; Jaya Santhi, R. (Asian Journal of Chemistry, 2021)
The chemical oxidative polymerization of poly(o-aminothiophenol) and poly(o-aminothiophenol)/CuO nanocomposites were performed in aqueous HCl using ammonium persulfate as an oxidant. The synthesized polymer and its CuO nanocomposites were characterized by employing FT-IR, UV-Vis and XRD analysis. Weight loss and electrochemical techniques were used to investigate the inhibitory performance of poly(o-aminothiophenol) and poly(o-aminothiophenol)/CuO nanocomposites on mild steel in 1 M HCl solution. The electrochemical impedance spectroscopic method showed a capacitive loop, revealing that the corrosion reaction is governed by the charge transfer mechanism. The inhibitors were of a mixed type, according to polarization measurements. The adsorption process was obeyed by the Langmuir isotherm. The Langmuir adsorption isotherm was also used to derive thermodynamic adsorption parameters.